Penerapan Inovasi Tirai Isolasi Mandiri Pasien Covid-19 - Mangalla, Lukas K.; Simatupang, Minson; Samhuddin, Samhuddin; Kadir, Kadir; Kadir, Abd. (Vokasi Universitas Halu Oleo, 2020)
The world is currently facing the biggest problem on new corona virus diseases called Covid-19. The rapid increase in the number of cases has challenged governments and experts to provide solutions for a lot patients infected by this virus such as medical treatments and health infrastructures. One of the effort to break the chain of transmission of the virus has been made by lecturers and students of Universitas Halu Oleo through the community service program. This program aims to increase the awareness of the community during the outbreak of Covid-19 as well as to introduce an important health infrastructure device called Independent Isolation Curtain for Covid-19 Patient (TIMPA Covid-19). This device can be used at home to localize the droplet spreading from patients when coughing or sneezing. The method of implementing this program consists of enlightened the community as well as educated the people on how to prevent their family from Covid-19 transmissions. The activity was also provided the device TIMPA Covi-19 model as well as showed the instruction of using it at home. This activity was conducted at Balai Desa Pambulaa Jaya Konawe Selatan with involving the village officials and all community members. The result of this program shows that the community have a good understanding and well improvement of knowledge on the basic rules of Covid-19 protection and how to isolate independently the patients of Covid-19 at home. In addition, the community can also understand how to make simple and affordable devices for self-isolation equipment of covid-19 patient.Kata Kunci: Curtain, Independent isolation, Prevention, Patient and Covid-19